Cholangiocarcinoma in Magnetic Resonance Cholangiopancreatography and Fascioliasis in Endoscopic Ultrasonography - Alizadeh, Amir Houshang Mohammad (S. Karger AG, 2011)
Fascioliasis is a worldwide zoonotic infection with Fasciola hepatica and Fasciola gigantica. The zoonoses are particularly endemic in sheep-raising countries and are also endemic in Iran. Typical symptoms that may be associated with fascioliasis can be divided by phases of the disease, including the acute or liver phase, the chronic or biliary phase, and ectopic or pharyngeal fascioliasis. Cholestatic symptoms may be absent, and in some cases diagnosis and treatment may be preceded by a long period of abdominal pain, eosinophilia and vague gastrointestinal symptoms. We report a case with epigastric and upper quadrant abdominal pain for the last 4 years, with imaging suggesting cholangiocarcinoma. Considering a new concept of endoscopic ultrasonography, at last F. hepatica was extracted with endoscopic retrograde cholangiography.